Effect of crystalline structure on the electrochemical properties of K0.25V2O5 nanobelt for fast Li insertion. (10th November 2016) - Fang, Guozhao; Liang, Caiwu; Zhou, Jiang; Cai, Gemei; Liang, Shuquan; Liu, Jun
Graphical abstract: We report the synthesis of aggregated K0.25 V2 O5 nanobelts with optimal crystalline structure. The formation of this hierarchical architecture is proposed by a partial melting and self-alignment mechanism. This material exhibits high discharge capacities at high rates and superior long-term cycling performance up to 800 cycles with no capacity loss. Highlights: Aggregated K0.25 V2 O5 nanobelts are prepared and investigated as cathode for lithium batteries. We demonstrate that an optimum treatment can improve the crystalline structure and the morphology. We propose a partial melting and self-alignment mechanism to produce the orderly nanobelts. This material exhibits high discharge capacity, high-rate capability and long-term cyclic stability. Abstract: Lithium vanadium oxides and vanadates have wide attention as cathode materials for Li ion battery applications, but there has been limited study on other cations substituted vanadium compounds, which could have favorable electrochemical properties. Here we report the synthesis and electrochemical properties of aggregated K0.25 V2 O5 nanobelts and the optimization of the crystalline structure for fast Li ion insertion. We propose a partial melting and self-alignment mechanism to produce the aggregated nanobelts. This material can deliver a high discharge capacity of 232 mA h −1 at 100 mA g −1 and high rate capability. It also exhibits superior long-term cycling performance with no capacity fading over 800 cycles at high current density of 1, 1.5, and 2 A g −1 . Remarkably, although some work has been devoted to potassium vanadates, there is little work introducing this class of materials with super long lifespan. The results demonstrate that the as-prepared K0.25 V2 O5 would be a potential candidate for LIBs.